Medicaid Expansion and the Unemployed - Thomas C. Buchmueller; Helen Levy; Robert G. Valletta (Institute of Labor Economics (IZA), 2019)
We examine how a key provision of the Affordable Care Act – the expansion of Medicaid eligibility – affected health insurance coverage, access to care, and labor market transitions of unemployed workers. Comparing trends in states that implemented the Medicaid expansion to those that did not, we find that the ACA Medicaid expansion substantially increased insurance coverage and improved access to health care among unemployed workers. We then test whether this strengthening of the safety net affected transitions from unemployment to employment or out of the labor force. We find no meaningful statistical evidence in support of moral hazard effects that reduce job finding or labor force attachment.
Keywords: J64; J68; I13; I18; 330; medicaid; insurance coverage; access to care; unemployment; labor force transitions